2022
DOI: 10.18063/ijb.v8i2.544
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed β-Tricalcium Phosphate Scaffolds Promote Osteogenic Differentiation of Bone Marrow-Deprived Mesenchymal Stem Cells in an N6-methyladenosineDependent Manner

Abstract: Bone defect is a serious orthopedic disease which has been studied for a long time. Alternative degradable biomaterials are required for bone repairing and regeneration to address the limitation of autogenous bone. β-tricalcium phosphate (β-TCP) is an alternative material with good cytocompatibility and has been used in bone defect treatment. However, whether β-TCP contributes to osteogenesis of bone marrow stem cells (BMSCs) through N6-methyladenosine (m6A) modification remains unknown. To address this issue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The promising results from various clinical trials underscore the efficacy of β-TCP in bone repair, demonstrating outcomes comparable to allografts. 52 Our results showed that compared with the PCL scaffold, the PCL/β-TCP scaffold can effectively promote osteogenic differentiation of MC3T3 cells ( Figure 3 ). Moreover, our in vivo and in vitro results showed that the PCL/β-TCP/SA/MT group exhibited the best osteogenic ability ( Figures 3 and 7 ) compared to the other groups under diabetic conditions, which aligns with the findings of prior investigations.…”
Section: Discussionmentioning
confidence: 72%
“…The promising results from various clinical trials underscore the efficacy of β-TCP in bone repair, demonstrating outcomes comparable to allografts. 52 Our results showed that compared with the PCL scaffold, the PCL/β-TCP scaffold can effectively promote osteogenic differentiation of MC3T3 cells ( Figure 3 ). Moreover, our in vivo and in vitro results showed that the PCL/β-TCP/SA/MT group exhibited the best osteogenic ability ( Figures 3 and 7 ) compared to the other groups under diabetic conditions, which aligns with the findings of prior investigations.…”
Section: Discussionmentioning
confidence: 72%
“…33 However, Jiao et al reported that the use of stem cells along with the printed scaffolds composed of beta-tricalcium phosphate could help the stability of the enzymes and biological mechanisms effective in repair and bone formation, and its use is suggested for bone repair. 34 Despite the results of this study, the identification of surgical treatments with high effectiveness in healing large bone defects remains a challenge. The 3D printed scaffolds composed of betatricalcium phosphate, which are associated with unique biological and molecular properties, can be effective in increasing effectiveness of surgical treatment, but larger studies are still needed.…”
Section: Discussionmentioning
confidence: 94%
“…The increased osteogenesis of BMSCs by m 6 A modification could also be used in the treatment of bone defects combined with degradable biomaterials. Compared to the control group, BMSCs stimulated by β-tricalcium phosphate (β-TCP) exhibited considerably greater expression of METTL3, which influences m 6 A modification of RNA in BMSCs and improves the stability of RUNX2 mRNA [ 151 ]. In animal bone defect models, Jiao et al.…”
Section: A Modification In Musculoskeletal Disordersmentioning
confidence: 99%
“…In animal bone defect models, Jiao et al. [ 151 ] discovered that β-TCP increased the m 6 A alteration of RUNX2, which stimulated the production of new bone. Han and colleagues [ 152 ] revealed similar results by using mesenchymal stem cells of the apical papillas (SCAPs), odontogenic MSCs with strong osteo/odontogenic capacity.…”
Section: A Modification In Musculoskeletal Disordersmentioning
confidence: 99%